High-Intensity Static Stretching in Quadriceps Is Affected More by Its Intensity Than Its Duration - Takeuchi, Kosuke; Sato, Shigeru; Kiyono, Ryosuke; Yahata, Kaoru; Murakami, Yuta; Sanuki, Futaba; Yoshida, Riku; Nakamura, Masatoshi (Frontiers in Physiology, 2021)
A previous study reported that 3-minutes of high-intensity static stretching at an intensity of 120% of range of motion did not change the muscle stiffness of the rectus femoris, because of the overly high stress of the stretching. The purpose of this study was to examine the effects of high-intensity static stretching of a shorter duration or lower intensity on the flexibility of the rectus femoris than that of the previous study. Two experiments were conducted (Experiment 1 and 2). In Experiment 1, eleven healthy men underwent static stretching at the intensity of 120% of range of motion for two different durations (1 and 3 minutes). In Experiment 2, fifteen healthy men underwent 3-minutes of static stretching at the intensity of 110% of range of motion. The shear elastic modulus of the quadriceps were measured. In Experiment 1, range of motion increased in both interventions (p < 0.01), but the shear elastic modulus of the rectus femoris was not changed. In Experiment 2, range of motion significantly increased (p < 0.01), and the shear elastic modulus of the rectus femoris significantly decreased (p < 0.05). It was suggested that the stretching intensity (110%) is more important than stretching duration to decrease the muscle stiffness of the rectus femoris.